English aristocratic women and the fabric of piety, 1450-1550 - Harris, Barbara J. (Gendering the late medieval and early modern world, 2018)
"The role played by women in the evolution of religious art and architecture has been largely neglected. This study of upper-class women in the fifteenth and sixteenth centuries corrects that oversight, uncovering the active role they undertook in choosing designs, materials, and locations for monuments, and commissioning repairs and additions to many of the parish churches, chantry chapels, and almshouses characteristic of the English countryside. Their preferred art, Barbara J. Harris shows, reveals their responses to the religious reformation and signifies their preferred identities."--Back cover